2017
DOI: 10.4238/gmr16039714
|View full text |Cite
|
Sign up to set email alerts
|

Research Article Antioxidant activity and chemical composition of oleoresin from leaves and flowers of Brunfelsia uniflora.

Abstract: ABSTRACT. In this study, the temperature and pressure of supercritical CO 2 extraction were evaluated to obtain oleoresin of Brunfelsia uniflora leaves and flowers. The oleoresin compounds were identified by gas chromatography-mass spectrometry. The antioxidant activity was evaluated by three different methods. The highest oleoresin yields were 3.32% at 40°C and 200 bar for the leaves, and 1.03% at 60°C and 200 bar for the flowers. The main extracted compounds from leaves were phytol varying from 11.95 to 36.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
0
8
0
1
Order By: Relevance
“…Studies carried out by our research group show that the yield of B. uniflora flower oleoresin obtained by supercritical carbon dioxide varies from 0.83 to 1.03%. However, according to Jorge (2016) the essential yield oil of B. uniflora by hydrodistillation is close to zero.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Studies carried out by our research group show that the yield of B. uniflora flower oleoresin obtained by supercritical carbon dioxide varies from 0.83 to 1.03%. However, according to Jorge (2016) the essential yield oil of B. uniflora by hydrodistillation is close to zero.…”
Section: Discussionmentioning
confidence: 92%
“…Jorge (2016) reported that the pressure increase from 150 to 200 bars of supercritical carbon dioxide increases the extraction of geranyllinalool from 11.72 to 21.52% in oleoresin. Zrira et al (2008) reported that extraction yield of A. visnaga oleoresin was greater (1.5%) by supercritical carbon dioxide when compared to hydrodistillation (0.4%).…”
Section: Discussionmentioning
confidence: 99%
“…However, similar activity was also observed against the non-carcinoma cell line HaCaT, indicating that it may not possess cancer-specific antiproliferative activity, although further studies are required. Although main components of the EO have been reported as main constituents in other plant extracts with similar biological activities [ 43 , 44 , 45 ], there are no available studies on the biological activities of the individual compounds, which is a valid area of further investigation. Overall, the results of our study indicated that EO form S. raeseri subsp.…”
Section: Discussionmentioning
confidence: 99%
“…The FRAP reagent was prepared fresh daily by mixing of 25 mL acetate buffer, 2.5 mL of 10 mM TPTZ solution, and 2.5 mL of 20 mM FeCl3 6H2O solution and warmed to 37°C in a water bath until used for the experiments. 17 The 50 µL of 250 µg/mL D. alatus oleoresin samples (OD1-OD5), Trolox or 100 µg/mL of standard (-)-ISSN 2616-0692 (Electronic) 852 © 2021 the authors. This work is licensed under the Creative Commons Attribution 4.0 International License α-gurjunene in methanol were mixed with 150 µL of the FRAP reagent for 30 min in the dark condition.…”
Section: Ferric Reducing Antioxidant Power (Frap) Assaymentioning
confidence: 99%